2004
DOI: 10.1536/jhj.45.103
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular and Tricuspid Valve Function in Patients With Two Ventricular Pacemaker Leads

Abstract: SUMMARYExisting data on the effect of retained pacemaker leads on right ventricular (RV) and tricuspid valve function is limited.Objective: In this echocardiographic study we investigated the long-term effect of retained ventricular leads on RV and tricuspid valve function in patients with permanent pacemakers.Forty patients, 18 with two (group I) and 22 with one (group II) ventricular lead were assessed echocardiographically at an average of 39 months after the second lead implantation in group I and 80 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…We did not find a difference in TR grade related to the number of leads implanted, and the published data in this regard are also controversial. Among 40 patients, Celiker et al found no difference in the degree of TR whether one or two leads were implanted, though the study was limited by a lack of preimplantation echocardiograms . On the other hand, Postaci et al found that more patients with two leads had grade 3+ TR (55.6%) compared with those patients with only one lead (55.6 vs 9.4%, P , 0.05) …”
Section: Discussionmentioning
confidence: 68%
“…We did not find a difference in TR grade related to the number of leads implanted, and the published data in this regard are also controversial. Among 40 patients, Celiker et al found no difference in the degree of TR whether one or two leads were implanted, though the study was limited by a lack of preimplantation echocardiograms . On the other hand, Postaci et al found that more patients with two leads had grade 3+ TR (55.6%) compared with those patients with only one lead (55.6 vs 9.4%, P , 0.05) …”
Section: Discussionmentioning
confidence: 68%
“…However, 1 of the main limitations of the study is the absence of echocardiographic assessment of the tricuspid valve prior to lead implantation. 14 On the other hand, Postaci and colleagues found that patients with 2 device leads have more grade 3 TR, present in 55.6% of patients with 2 ventricular leads, compared to 9.4% in those with 1 lead (P < 0.05). 15 In the pediatric population, it was found that a risk factor for lead-related TR was congenital heart disease that is not right sided.…”
Section: Predictors Of Tr After Device Implantationmentioning
confidence: 94%
“…15 However, other studies have not found a significant relationship between number of leads and TR. 8,31 Therefore, while some studies have shown worse TR associated with multiple leads crossing the tricuspid annulus, this has not been universally demonstrated and does not seem to have adverse clinical or hemodynamic consequences.…”
Section: 68%mentioning
confidence: 99%